Catholic Identity and the Revolt of the Netherlands. A View from South of the Border (discussiedossier over Catholic Identity and the Revolt of the Netherlands, 1520-1635) - Diefendorf, B.B. (BMGN - Low Countries Historical Review, 2011)
Pollmann, Judith, Catholic Identity and the Revolt of the Netherlands 1520-1635 (Past and Present; Oxford: Oxford University Press, 2011, xiv + 239 blz., ISBN 978 0 19 960991 8). Judith Pollmann (Catholic Identity and the Revolt of the Netherlands, 1520-1635) argues persuasively that Netherlandish Catholics were slow to oppose the spread of heresy because their clergy encouraged passivity rather than resistance. This behavior contrasts strikingly with the active resistance posed to the spread of Calvinism in France and challenges French historians to question the assumption that violence was a natural response to the fracturing of community brought about by religious schism. Explanations of popular religious violence must nevertheless also consider their respective political contexts and the extent to which people trusted their rulers to suppress the threat of heresy. Pollmann’s further argument that the stunning Catholic revival that occurred in the Southern Netherlands could only occur when the clergy accepted the need to collaborate with pious lay people is also persuasive but might have been enriched by more consideration of the emergence of Catholic identities in Wallonia and among women. This review is part of the discussion forum 'Catholic Identity and the Revolt of the Netherlands 1520-1635' (Judith Pollmann).